STEM Teacher Leader Collaborative: A Responsive Professional Learning Network With Radical Hope - Mercier, Alison (Innovations in Science Teacher Education, 2022)
Many elementary teachers in the United States receive little to no STEM-focused professional learning during an average school year. When elementary teachers do participate in professional learning opportunities focused solely on STEM teaching and learning, they are often positioned as novices in need of improvement or instruction rather than colearners and cocontributors to the learning community. In this article, I describe the STEM Teacher Leader Collaborative as one way to address current challenges in STEM-focused professional learning and as an infrastructure for responsive teacher learning. I highlight the STEM Teacher Leader Collaborative as a model of a responsive professional learning network with radical hope, describing its guiding principles and the meanings teachers make of their experience within the network.